Metrological Comparison between Heterogeneous Surfaces and their Imprints - Kubisova, Milena; Novak, Martin; Koutnak, Rostislav; Vrbova, Hana; Zaludek, Milan; Knedlova, Jana (Manufacturing Technology Journal, 2022)
This article seeks to compare roughness characteristics of surfaces created through unconventional machining technologies, specifically utilizing plasma and laser. Cuts of different thickness of material were taken for this purpose. Furthermore, the article presents an evaluation of surfaces obtained from an impression material SILOFLEX(R), followed by the determination of similarities between these impressions and original surfaces. In this work, we mainly aimed to statistically find and determine the differences inbetween the evaluation of surfaces in concert with ISO 4287, ISO 4288, and ISO 25 178. Next, investigation analysis of the machined and replicated surfaces was done utilizing the contactless profilometer and the follow-up statistical evaluation of measured data from compared surface groups.
Keywords: Surface Structure; Surface Measurement; Non-conventional Technologies; Anova